EFEKTIVITAS PELAKSANAAN PEMBANGUNAN DAN PEMELIHARAAN JALAN OLEH BALAI BESAR PELAKSANAAN JALAN NASIONAL V DI PROVINSI SUMATERA SELATAN - Herlina . Martauli S; Andri Andri; Dedi Apriansah; Kamaludin Kamaludin; Tati Juriani (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2022)
This study aims to analyze the effectiveness of the implementation of road construction and maintenance by the National Road Implementation Center V in South Sumatra Province. The formulation of the problem in this research is how effective the implementation of road construction and maintenance by the National Road Implementation Center V in South Sumatra Province is. This study uses a qualitative method with a descriptive approach. Qualitative research procedures produce descriptive data in the form of written or spoken words from people and observable behavior. The approach is directed at the background and the individual holistically (whole). So, in this case it is not permissible to isolate individuals or organizations into variables or hypotheses, but it is necessary to view them as part of a whole, (Lexy J. Moleong, 2005: 4). The results of the study indicate that an increase in quantity will be related to output performance as well as controlling or controlling costs. The costs incurred for a road or bridge infrastructure program have been calculated based on existing studies. In addition, suitability in terms of length, width, implementation time and location will also be related to the use or utilization of roads in helping community activities in the social, economic and other fields. The quality and cost of road construction has supported economic growth both nationally and in the regions it passes through. Where the quality of construction of widening and strengthening structures, handling of segments that have been prone to accidents, as well as institutions through three steps will be carried out namely re-activating the foreman/road observer who will be included in the construction contract.